Leitura de contos no ensino fundamental: a contribuição da Teoria Literária nesse processo - Luciéle Bernardi de Souza; Liane Batistela Kist (Universidade do Estado do Rio Grande do Norte, 2013)
We propose, through a literature review and considerations of praxis developed in the classroom, investigate how literary theory contributes to the reading practices of short stories in elementary school. The aim of this paper is to contribute to the expansion of discussion and reflection on the Methodology for Teaching Literature and Reading in Basic Education. As theoretical scope, we will use the Reception Aesthetics theorists and thinkers Brazilians as Yunes (1995), Aguiar & Bordini (1993), among others. The considerations presented concern the teaching experience developed within the discipline of Supervised Portuguese / Undergraduate and Supervised Internship in elementary school-Portuguese. We can say, at the end of my reflection on teaching practice, the relationship of knowledge, when established between university and school, is of great value to an understanding of the literary work of art and the consequent decrease of the Basic School student with such work.